Comparing Word Elicitation Strategies for Individuals With Apraxia of Speech and Aphasia. - Van Sickle, Angela; Dembowski, James; Corwin, Melinda (International Journal of Language & Communication Disorders (John Wiley & Sons, Inc.))
Introduction: Following a stroke, some individuals experience aphasia, apraxia of speech (AOS), or both. When these disorders are severe, it can be challenging to determine whether the observed deficits stem from disruptions in linguistic–symbolic processes, as seen in aphasia, or from impairments in motor planning, as characteristic of AOS. Sentence completion may be a strategy for improving word production that may facilitate both symbolic‐linguistic and motor processes for persons with acquired aphasia and AOS. Aims: To evaluate word production in individuals with aphasia and AOS using two conditions: repetition alone and repetition combined with a sentence completion task. Methods: Eight participants with AOS and aphasia produced bisyllabic words in two conditions, repetition only and repetition plus sentence completion, to determine the effectiveness for eliciting accurate production of target words. Results: A one‐tailed Wilcoxon signed‐rank test revealed that scores for the sentence completion condition were significantly higher than the repetition condition. Results were significant for whole word production (p = 0.014) and partial word production (p = 0.015). Conclusions: Participants accurately produced significantly more target words using repetition plus sentence completion versus repetition alone. Repeated accurate productions may support and enhance motor learning. Sentence completion is a potential clinical tool for eliciting accurate productions of functional target words. WHAT THIS PAPER ADDS: What is already known on this subjectMany studies using sentences to improve word production included participants with aphasia only or aphasia and acquired apraxia of speech (AOS). A small number of studies have examined top‐down, sentence‐level cueing approaches to AOS therapy with encouraging results.What this paper adds to existing knowledgeThis paper examined word production in eight participants with aphasia and AOS across two elicitation contexts—repetition alone and repetition combined with a sentence completion task—to identify which strategy yields a higher rate of correct productions. This study isolated the motor processes involved in word production by removing the need for lexical retrieval, thereby controlling for the challenge of distinguishing word‐finding deficits from motor control deficits in speakers with both aphasia and AOS.What are the potential or actual clinical implications of this study?Potential implications of this study include identifying an effective strategy for eliciting accurate word production for people with chronic, severe expressive aphasia and AOS, which can be applied consistently to support motor learning and improve single‐word production.